A case study on Monday blues in Ranhill Bersekutu Sdn Bhd / Nur Aidah Sulaiman - Sulaiman, Nur Aidah (2010)
Monday blues is a bad environment and every organization will experienced this symptoms. Even this scenario is not classified as a major problem in the company but this problem should be addressed at an early stage in order to prevent from getting worst besides it can give a bad reputation to the employees and the company itself. Therefore, to avoid the feeling Monday blues among the employees, research should be conducted to identify the causes, reasons and the solutions of the problems that occur. After research has been conducted, Monday blues also happens to employees in Ranhill Bersekutu Sdn Bhd but it is still under control. This can be proven when Monday is the day that most employees take a leave besides Monday also had the highest percentage of latecomers other than the other days. Apart from that, based on interviews conducted with employers and observation made, it shown that employee in Ranhill Bersekutu Sdn Bhd is also having Monday blues.